The Effects Of Functıonal Treatment On The Sagıttal Locatıon Of Mandıbular Condyl - Erhan Özdiler (Galenos Yayinevi, 1991)
The purpose of this study was to examine the effects of U-Bügel Type I activator and conventional activator of functional appliances used for the treatment of Cl II, I anomalies in the growth period, by considering the sagittal direction of the mandibular condyl and its environs. The changes of the amount and the direction of growth of the mandibular condyl, would effect the ramal inclination and consequently the whole mandible. This situation however is of significance in sense of stability and prognose of the treatment This study was made on the onset and the final lateral cephalograms, and hand-wrist graphics of 49 individuals with skeletal and dental Angle Cl II, I malocclusion. although, Cl II, I anomaly was corrected by functional therapy and also the overjet was eliminated, in the statistical estimations of the condyl in sagittal direction no significant findings could be obtained.